A Southern-Sky Total Intensity Source Catalogue at 2.3 GHz from S-Band Polarisation All-Sky Survey Data - Meyers, B.; Hurley-Walker, Natasha; Hancock, Paul; Franzen, Thomas; Carretti, E.; Staveley-Smith, L.; Gaensler, B.; Haverkorn, M.; Poppi, S. (Cambridge University Press, 2017)
Copyright © Astronomical Society of Australia 2017The S-band Polarisation All-Sky Survey has observed the entire southern sky using the 64-m Parkes radio telescope at 2.3 GHz with an effective bandwidth of 184 MHz. The surveyed sky area covers all declinations d ? 0°. To analyse compact sources, the survey data have been re-processed to produce a set of 107 Stokes I maps with 10.75 arcmin resolution and the large scale emission contribution filtered out. In this paper, we use these Stokes I images to create a total intensity southern-sky extragalactic source catalogue at 2.3 GHz. The source catalogue contains 23 389 sources and covers a sky area of 16 600 deg2, excluding the Galactic plane for latitudes |b| < 10°. Approximately, 8% of catalogued sources are resolved. S-band Polarisation All-Sky Survey source positions are typically accurate to within 35 arcsec. At a flux density of 225 mJy, the S-band Polarisation All-Sky Survey source catalogue is more than 95% complete, and ~ 94% of S-band Polarisation All-Sky Survey sources brighter than 500 mJy beam-1 have a counterpart at lower frequencies.